Teacher Engagement in Education for Sustainability: Integrating Anti-Corruption Values into Learning in Remote Areas - Monica Tiara; Irwan Irwan; Relly Anjar Vinata Wisnu Saputra; Muhammad Faisal (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
Corruption remains a major obstacle to sustainable development, highlighting the importance of educational approaches that cultivate integrity from an early age. Although anti-corruption education has been integrated into the Indonesian school curriculum, its implementation remains inconsistent, particularly in remote schools facing geographical constraints and limited educational resources. This study explores how teacher engagement supports the integration of anti-corruption values into classroom learning within the framework of Education for Sustainability. A qualitative multiple-case study was conducted in three public junior secondary schools in remote areas of West Sumatra, Indonesia. Data were collected through in-depth interviews with school principals and teachers, classroom observations, and reflective group discussions with students, and analyzed using thematic analysis. The findings identified four interconnected dimensions of teacher engagement: teachers' conceptual readiness, structural and institutional conditions, contextual pedagogical strategies, and student integrity development. Based on these findings, the study proposes a Teacher Engagement Framework for Sustainable Integrity Development, demonstrating that teacher engagement functions as the key pedagogical mechanism linking anti-corruption education with Education for Sustainability. The framework provides both a conceptual contribution to the literature and practical implications for strengthening teacher professional development and integrity education in remote schools.